Digital image watermaking using redundant wavelet transform for copyright protection - Lim, Say Yarn (2007)
The concern of the digital image copyright management raised the research interest all over the world recently. One of the methods to protect our copyright of digital image is using the watermarking technique. Watermarking technique hides digital copyright information into the digital images imperceptibly. This digital copyright information can be extracted for the verification purpose when a copyright issue was in question. A new redundant wavelet transform based digital image watermarking scheme was introduced. Redundant wavelet transform is used in the watermark embedding process because of its property that the size of coefficients remains the same as the original image after decomposition process. This increases the capacity of the watermarks that can be embedded into one image. Besides that, as commonly known, watermark information which is embedded in frequency domain is more robust to attacks. Logo-based watermark is used in the watermarking scheme so that it can easily be identified during the verification process. The watermarks are embedded by adaptively modifying a block of redundant wavelet transform coefficients. This redundant wavelet transform watermarking scheme can be used on gray scale images and color images. The properties of the watermarking scheme such as the perceptual quality of the watermarked images and robustness were tested. Besides that, a benchmark tool, StirMark, is applied to watermarked images to evaluate the performance of the watermarking scheme. The experimental result showed that the watermarking scheme produced a good perceptual quality of the watermarked image and possessed its robustness to some common image processing attacks.